An equation is shown below:

4(x − 3) − 5(x + 1) = 3

Which statement shows a correct next step in solving the equation? (1 point)

Group of answer choices

The equation can become 4x − 12 − 5x − 5 = 3 by applying the associative property of multiplication.

The equation can become 4x − 3 − 5x + 1 = 3 by applying the associative property of multiplication.

The equation can become 4x − 3 − 5x + 1 = 3 by applying the distributive property.

The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property.

Respuesta :

Answer:

The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property.

Step-by-step explanation:

4(x − 3) − 5(x + 1) = 3

The first thing would be distribute the 4 and the 5 respectively

4x-12 -5x-5 =3